Interest in Integrative Medicine Among Postmenopausal Hormone Receptor–Positive Breast Cancer Patients in the EvAluate-TM Study. (June 2017) - Hack, Carolin C.; Fasching, Peter A.; Fehm, Tanja; de Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; Wuerstlein, Rachel; et al.
Background . Breast cancer patients often use complementary and alternative medicine, but few prospectively collected data on the topic are available specifically for postmenopausal breast cancer patients. A large prospective study was therefore conducted within a noninterventional study in order to identify the characteristics of patients interested in integrative medicine. Methods . The EvAluate-TM study is a prospective, multicenter noninterventional study in which treatment with the aromatase inhibitor letrozole was evaluated in postmenopausal women with hormone receptor–positive primary breast cancer. Between 2008 and 2009, 5045 postmenopausal patients were enrolled at 339 certified breast centers in Germany. As part of the data collection process, patients were asked at the baseline about their interest in and information needs relating to integrative medicine. Results . Of the 5045 patients recruited, 3411 responded to the questionnaire on integrative medicine and took part in the analysis, 1583 patients expressed an interest in integrative medicine, and 1828 patients declared no interest. Relevant predictors of interest in integrative medicine were age, body mass index, tumor size, previous chemotherapy, and use of concomitant medications for other medical conditions. Interest in integrative medicine declined highly significantly ( P < .001) with age (<50 years, 74.1%; 50-60 years, 54.1%; >65 years, 38.0%). Patients in favor of integrative medicine were significantly less satisfied with the information received about individual treatments and antihormonal therapy. Patients with interest in integrative medicine were more often interested in rehabilitation and fitness, nutritional counseling, and additional support from self-help organizations. These women were mostly interested in receiving information about their disease and integrative medicine from a physician, rather than from other sources. Conclusions . This study shows that a considerable proportion of postmenopausal breast cancer patients are interested in integrative medicine. Information about integrative medicine should therefore be provided as part of patient care for this group. It was found that receiving concomitant medication for other medical conditions is one of the main predictors for women not being interested in integrative medicine. This group of patients may need special attention and individualized information about integrative medicine. Additionally, most patients were interested in obtaining the relevant information from their doctor.